Canadian Rhinology Working Group consensus statement: biologic therapies for chronic rhinosinusitis - Andrew Thamboo; S. Kilty; I. Witterick; Y. Chan; C. J. Chin; A. Janjua; A. Javer; J. Lee; E. Monterio; B. Rotenberg; J. Scott; K. Smith; et al. (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Recent evidence suggests that biologic therapy with targeted activity within the Type 2 inflammatory pathway can improve the clinical signs and symptoms of chronic rhinosinusitis with nasal polyposis (CRSwNP). There remains a population in CRSwNP that despite medical therapy and endoscopic sinus surgery have persistent signs and symptoms of disease. Therefore, biologics, monoclonal antibody agents, could be beneficial therapeutic treatments for these patients. There have been eight randomized, double-blind, placebo-controlled trails performed for CRSwNP targeted components of the Type 2 inflammatory pathway, notably interleukin (IL)-4, IL-5 and IL-13, IL-5R, IL-33, and immunoglobulin (Ig)E. However, there are no formal recommendations for the optimal use of biologics in managing Chronic Rhinosinusitis (CRS) within the Canadian health care environment. Methods A Delphi Method process was utilized involving three rounds of questionnaires in which the first two were completed individually online and the third was discussed on a virtual platform with all the panelists. 17 fellowship trained rhinologists across Canada evaluated the 28 original statements on a scale of 1–10 and provided comments. A rating within 1–3 indicated disagreement, 8–10 demonstrated agreement and 4–7 represented being neutral towards a statement. All ratings were quantitively reviewed by mean, median, mode, range and standard deviation. Consensus was defined by removing the highest and lowest of the scores and using the “3 point relaxed system”. Results After three rounds, a total of 11 statements achieved consensus. This white paper only contains the final agreed upon statements and clear rationale and support for the statements regarding the use of biologics in patients with CRS. Conclusion This white paper provides guidance to Canadian physicians on the use of biologic therapy for the management of patients with CRS, but the medical and surgical regimen should ultimately be individualized to the patient. As more biologics become available and additional trials are published we will provide updated versions of this white paper every few years. Graphical abstract